1998
DOI: 10.1080/000368498325796
|View full text |Cite
|
Sign up to set email alerts
|

Parimutuel wagering and video gaming: a racetrack portfolio

Abstract: Parimutuel wagering has been declining for several decades due, in part, to increased competition from state lotteries and casino gaming. In recent years, an attempt has been made to integrate video lottery terminal (VLT) gaming into a parimutuel racetrack's product portfolio. Daily data are used to develop product demand equations for parimutuel horse-race wagering and video lottery gaming at a throughbred racetrack. It is found that introduction of VLTs into the product mix results in decreased parimutuel wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…As was the case with studies on the substitutionary impacts of casinos on pari-mutuel and race betting, lotteries have also been argued to be partially responsible for the decline of racing industries (Thalheimer, 1998). The available evidence seems to support this suggestion, as most studies have found that lotteries cannibalize pari-mutuel and racing wagers both by a patronage effect and by a spending effect (Gulley & Scott, 1989;Miers, 1996;Mobilla, 1992;Simmons & Sharp, 1987;Thalheimer & Ali, 1995a, 1995bVasche, 1990).…”
Section: Lotteriessupporting
confidence: 47%
See 4 more Smart Citations
“…As was the case with studies on the substitutionary impacts of casinos on pari-mutuel and race betting, lotteries have also been argued to be partially responsible for the decline of racing industries (Thalheimer, 1998). The available evidence seems to support this suggestion, as most studies have found that lotteries cannibalize pari-mutuel and racing wagers both by a patronage effect and by a spending effect (Gulley & Scott, 1989;Miers, 1996;Mobilla, 1992;Simmons & Sharp, 1987;Thalheimer & Ali, 1995a, 1995bVasche, 1990).…”
Section: Lotteriessupporting
confidence: 47%
“…Pari-mutuel betting has been declining in many Western contexts for a long time. Some authors have attributed this decline to the cannibalizing effects of the expansion of casino gambling and state lotteries since the 1980s (e.g., Thalheimer, 1998), and the available evidence seems to support this view.…”
Section: /4mentioning
confidence: 73%
See 3 more Smart Citations